Adventures of Allegra Fullerton : Or, A Memoir of Startling and Amusing Episodes from Itinerant Life--A Novel - Begiebing, Robert J., 1946- (Book collections on Project MUSE., 2012)
A picaresque novel of the remarkable life of a liberated 19th-century woman.